2015
DOI: 10.1002/humu.22778
|View full text |Cite
|
Sign up to set email alerts
|

Update and Mutational Analysis ofSLC20A2: A Major Cause of Primary Familial Brain Calcification

Abstract: Primary familial brain calcification (PFBC) is a heterogeneous neuropsychiatric disorder, with affected individuals presenting a wide variety of motor and cognitive impairments, such as migraine, parkinsonism, psychosis, dementia, and mood swings. Calcifications are usually symmetrical, bilateral, and found predominantly in the basal ganglia, thalamus, and cerebellum. So far, variants in three genes have been linked to PFBC: SLC20A2, PDGFRB, and PDGFB. Variants in SLC20A2 are responsible for most cases identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 44 publications
3
53
1
2
Order By: Relevance
“…Loss-of-function mutations in SLC20A2 gene encoding the type III sodium-dependent phosphate transporter 2 (PiT-2) are also associated with Fahr's disease 67,68 , and likely involve changes in phosphate transport at the BBB that promote regional brain accumulation of inorganic phosphate that subsequently cause calcium phosphate deposition 67 .…”
Section: Pericyte-endothelial Signal Transductionmentioning
confidence: 99%
“…Loss-of-function mutations in SLC20A2 gene encoding the type III sodium-dependent phosphate transporter 2 (PiT-2) are also associated with Fahr's disease 67,68 , and likely involve changes in phosphate transport at the BBB that promote regional brain accumulation of inorganic phosphate that subsequently cause calcium phosphate deposition 67 .…”
Section: Pericyte-endothelial Signal Transductionmentioning
confidence: 99%
“…Recently, a new review (Lemos et al, 2015) reported a distribution of variants across the SLC20A2 gene: 55 variants present in 55 unrelated patient have been identified in families of diverse ethnicities and only few are recurrent.…”
Section: Discussionmentioning
confidence: 98%
“…The frequencies of theses variants in the patients' respective populations as estimated in ExAC are not inconsistent with a causative effect, as they are in the same frequency ranges as other disease-causing variants in SLC20A2 . 8 Because neither segregation nor functional data are available, it is not possible to conclude about their pathogenicity at this stage.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Heterozygous variants causing autosomal dominant PFBC in up to 50% of the families were identified in 4 genes: SLC20A2 , PDGFRB , PDGFB , and XPR1 . 48 We previously searched for genes with a cerebral expression pattern similar to the PFBC major causative gene SLC20A2 using the Allen Brain Atlas (brain-map.org/), 9,10 observing a higher SLC20A2 expression in regions affected by calcifications in PFBC. PCDH12 was singled out with the highest significant correlation, 10 and a follow-up analysis with additional brains still shows PCDH12 as the most similar pattern to SLC20A2 , even when compared with the other known PFBC causative genes (table e-1 at Neurology.org/ng).…”
mentioning
confidence: 99%